2021
DOI: 10.1101/2021.11.16.468792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial OPA1 deficiency causes reversible defects in adult neurogenesis-associated spatial memory in mice

Abstract: Mitochondria are integrative hubs central to cellular adaptive pathways. Such pathways are critical in highly differentiated post-mitotic neurons, the plasticity of which sustains brain function. Consequently, defects in mitochondrial dynamics and quality control appear instrumental in neurodegenerative diseases and may also participate in cognitive impairments. To directly test this hypothesis, we analyzed cognitive performances in a mouse mitochondria-based disease model, due to haploinsufficiency in the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Previous research has demonstrated that such biological changes enhanced cognitive functions like spatial memory in animals with various pathological conditions. 21,23,40 However, it remains unclear whether the upregulation of neurogenesis under normal physiological conditions affects hippocampus-related cognitive functions in adult mice. Our behavioral results demonstrated that UMI-77 increased the duration of spatial memory in adult mice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has demonstrated that such biological changes enhanced cognitive functions like spatial memory in animals with various pathological conditions. 21,23,40 However, it remains unclear whether the upregulation of neurogenesis under normal physiological conditions affects hippocampus-related cognitive functions in adult mice. Our behavioral results demonstrated that UMI-77 increased the duration of spatial memory in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dynamics, constituting essential mechanisms by which the organism safeguards mitochondrial function, serve as crucial regulatory factors in adult neurogenesis under pathological conditions. [20][21][22][23][24] However, their role as a modulator of neurogenesis during developmental processes remains unclear. Our results indicate that there is a decline in mitophagy from adolescence to adulthood, along with a simultaneous decrease in mitochondrial fusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations